Optimization of Alcohol Dehydrogenase for Industrial Scale Oxidation of Lactols. Issue 11 (6th September 2020) - Bartsch, Sebastian; Brummund, Jan; Köpke, Sabrina; Straatman, Harrie; Vogel, Andreas; Schürmann, Martin
Abstract: Alcohol dehydrogenases (ADH) are widely used to enantioselectively reduce ketones to chiral alcohols, but their application in industrial scale oxidations is rare. Reasons are the need for an NAD(P) + cofactor regeneration system, often low performance in oxidative reactions and the limited substrate scope of ADHs. ADHA from Candida magnoliae DSMZ 70638 is identified to efficiently catalyze the regio‐selective hydroxy‐lactone oxidations to hydroxy‐lactones. Hydroxy‐lactones are common intermediates in industrial processes to cholesterol lowering (va)statin drugs. A biocatalytic aliphatic hydroxy‐lactone oxidation process is developed using pure oxygen as oxidant reaching volumetric productivities of up to 12 g L −1 h −1, product concentrations of almost 50 g L −1 and 95% reaction yield. For co‐factor recycling a previously engineered, water‐forming NAD(P)H‐oxidase from Streptococcus mutans is used. The process is scaled up to industrial pilot plant scale and it could be demonstrated that ADH catalyzed oxidations can be developed to efficient and safe processes. However, the ADHA wild‐type enzyme is not productive enough in chlorolactol oxidation. Therefore, enzyme engineering and multi‐parameter screening is successfully applied to optimize the enzyme for the target reaction. The optimized ADHA variant shows a 17‐fold higher oxidative activity, a 26°C increased stability and is applied to develop an efficient chlorolactol oxidation process. Abstract : A very efficient and scalable oxidative alcohol dehydrogenase (ADH) process is developed to oxidise hydroxy‐lactols to hydroxy‐lactones, which are used as intermediates for cholesterol‐lowering drugs. This finally resulted in >3.5 kg produced hydroxy‐lactone on 100 L demonstration scale. The oxidative performance of the ADH is improved by enzyme engineering for a chlorinated hydroxy‐lactol 17‐fold and the thermostability by +26°C.